2009
DOI: 10.1111/j.1095-8649.2009.02333.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal location and distribution of As51 satellite DNA in five species of the genus Astyanax (Teleostei, Characidae, Incertae sedis)

Abstract: Constitutive heterochromatin makes up a substantial portion of the genome of eukaryotes and is composed mainly of satellite DNA repeating sequences in tandem. Some satellite DNAs may have been derived from transposable elements. These repetitive sequences represent a highly dynamic component of rapid evolution in genomes. Among the genus Astyanax, the As51 satellite DNA is found in species that have large distal heterochromatic blocks, which may be considered as derived from a transposable DNA element. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Satellite DNAs mobility, amplification, and potential to accumulate mutations play an important role in karyotype evolution, especially when these sequences are species-specific and/or chromosome-specific [Ugarkovic and Plohl, 2002] serving as potential tools for evolutionary and phylogenetic studies [Pons et al, 2002;Pons and Gillespie, 2003;Kantek et al, 2009;Vicari et al, 2010]. FISH with Cot-1 DNA probes showed that these repetitive fractions of the genome present a preferential centromeric location on the chromosomes of both species.…”
Section: Discussionmentioning
confidence: 99%
“…Satellite DNAs mobility, amplification, and potential to accumulate mutations play an important role in karyotype evolution, especially when these sequences are species-specific and/or chromosome-specific [Ugarkovic and Plohl, 2002] serving as potential tools for evolutionary and phylogenetic studies [Pons et al, 2002;Pons and Gillespie, 2003;Kantek et al, 2009;Vicari et al, 2010]. FISH with Cot-1 DNA probes showed that these repetitive fractions of the genome present a preferential centromeric location on the chromosomes of both species.…”
Section: Discussionmentioning
confidence: 99%
“…However, reassociation kinetics based on C o t-1 DNA and the microdissection of chromosomes submitted to C-banding and the subsequent amplification of heterochromatic sequences using degenerate oligonucleotide-primed polymerase chain reaction (PCR) have been used successfully. [9][10][11][12][13][14] The Parodontidae is a Neotropical fish group that is divided into three genera: Parodon, Apareiodon, and Saccodon. 15 Cytogenetic studies reported a conserved diploid number of 54 chromosomes in Parodontidae with distinctive karyotype formulae and numerical/position variation of 18S and 5S rDNA sites.…”
mentioning
confidence: 99%
“…1a). In Teleostei, chromosomespecific satellite DNA may be a useful cytogenetic marker (Saito et al 2007), and sometimes used to in resolving cytotaxonomic issues in species complexes such as that involving the Astyanax scabripinnis species group (Vicari et al 2008;Kantek et al 2009). Among belonids, the heterochromatin can be considered an important component in the karyotype diversification of the group.…”
Section: Discussionmentioning
confidence: 99%